Exploring Multiple Aspects of Taxonomic and Functional Diversity in Microphytobenthic Communities: Effects of Environmental Gradients and Temporal Changes - Teittinen, Anette; Virta, Leena (Frontiers in Microbiology, 2021)
Biodiversity has traditionally been quantified using taxonomic information but the importance of considering also functional characteristics has recently gained increasing attention among microorganisms too. However, studies exploring multiple aspects of taxonomic and functional diversity and their temporal variation are scarce for diatoms, one of the most important microbial groups in aquatic ecosystems. Here, our aim was to examine the taxonomic and functional alpha and beta diversity of diatoms in a coastal rock pool system characterized by naturally high environmental heterogeneity. We also investigated temporal differences in the diversity patterns and drivers. The relationship between species richness and functional dispersion was temporally coherent, such that species-poor communities tended to be functionally clustered. The trend between species richness and taxonomic uniqueness of community composition was temporally inconsistent, changing from negative to nonsignificant over time. Conductivity or distance to the sea or both were key determinants of species richness, functional dispersion and uniqueness of community composition. The increase of community dissimilarity with increasing environmental distance was stronger for taxonomic than functional composition. Our results suggest that even minor decreases in species richness may result in lowered functional diversity and decreased ecosystem functioning. Species-poor ecosystems may, however, have unique species compositions and high contributions to regional biodiversity. Despite changing species compositions along environmental gradients, communities may remain high functional similarity and robustness in the face of environmental changes. Our results highlight the advantage of considering multiple biodiversity metrics and incorporating a temporal component for a deeper understanding of the effects of environmental changes on microbial biodiversity.